2009
DOI: 10.1145/1644015.1644020
|View full text |Cite
|
Sign up to set email alerts
|

Approximating connectivity augmentation problems

Abstract: Let G = (V, E) be an undirected graph and let S ⊆ V . The S-connectivity λ S G (u, v) of a node pair (u, v) in G is the maximum number of uv-paths that no two of them have an edge or a node in S − {u, v} in common. The corresponding Connectivity Augmentation (CA) problem is: given a graph G = (V, E), a node subset S ⊆ V , and a nonnegative integer requirement function r(u, v) on V ×V , add a minimum size set F of new edges to G so that λ S G+F (u, v) ≥ r(u, v) for all (u, v) ∈ V ×V . Three extensively studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…As for LAP, Frank (1992Frank ( , 1994 showed that it ). * * 7/4-approximable if r depends only on W 2 (Nutov 2005), while solvable in O(n 3 |W 2 |(m + n log n)) time if in addition r ≥ 2 holds (Ishii and Hagiwara 2006). …”
Section: Previous Workmentioning
confidence: 99%
“…As for LAP, Frank (1992Frank ( , 1994 showed that it ). * * 7/4-approximable if r depends only on W 2 (Nutov 2005), while solvable in O(n 3 |W 2 |(m + n log n)) time if in addition r ≥ 2 holds (Ishii and Hagiwara 2006). …”
Section: Previous Workmentioning
confidence: 99%
“…It seems that this result of [13] cannot be deduced from our work, as the proof of the directed case is essentially the same as that of the undirected one. We also note that the hardness result in Corollary 1.3 was recently improved by Chakraborty, Chuzhoy, and Khanna [1] to a k ε -hardness of approximation for all k > k 0 , where ε, k 0 are universal constants.…”
Section: Introductionmentioning
confidence: 62%
“…In [13] it is proved that the same hardness result holds even for 0, 1-costs, for both directed and undirected graphs (for large values of k). It seems that this result of [13] cannot be deduced from our work, as the proof of the directed case is essentially the same as that of the undirected one.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations